FAKTOR PEYEBAB TERJADINYA DIRECT DAN INDIRECT WASTE PADA PROYEK BANGUNAN BERTINGKAT DI SURABAYA - Michella Beatrix (Fakultas Teknik, Universitas Wiraraja, 2021)
In construction projects, the occurrence of waste is something that will probably continue to happen. Waste that occurs can be large or small depending on the factors causing it and its impact, and this affects the implementation, especially for the contractor as a service provider. Many things can be a factor in the occurrence of waste, and cannot avoid. In the construction project of building in Surabaya, the occurrence of waste also often occurs and is influenced by several factors. Therefore this research focuses on the factors that cause construction waste (direct and serial waste) in projects of building in Surabaya. This study uses data distribution in the form of questionnaires to contractors in Surabaya with the limitation of company qualifications being medium to large contractor companies. Processing the questionnaire data that has been obtained using Multiple Regression Analysis. The results of this study are 3 factors that have the greatest influence on the occurrence of waste, namely the factor of handling, Other Factors, and Procurement Factors. The magnitude of these factors based on the research results is a handling factor of 35%, other factors at 23%, and a procurement factor of 17%.